Police organizational structure and policies and the socio-political culture of two communities in Iloilo City proper their influence on police strategy and discretion. - Dolendo, Sigrid Mae M.
This study examined how police beat officers behave and act accordingly and adaptively to fullfill their tasks as affected by political factors such as the established policies and organizational structure and the social-political character of the communities from where they operate. Utilizing key-informant interiews, community profiling, ocular inspection and secondary data reviews as data gathering methods, this research particularly addressed the following themes: (1)how the polic ebehaves in the field on the context of police discretion and strategy, (2)the influence of the police organizational structure, rules, and policies on police strategy and discretion, and (3)the influence of the "soci-opolitical culture" on police strategy and discretion., The beat officers are aware of the procedures they should follow set by the police organization in responding to a crime. However, police officers usually curb such protocols and procedures to suit the strategy of the law enforcer. The influence of the "socio-political culture" of the community is evident in that beat officers usually adapt to the kind and character of the community where they function. The officers would devise strategies through their own initiatvies taht would be adept and effective to the socio-political character of the community. The organizational structure, policies and rules of the police precinct are limited to creating guidelines to harness police jobs and check police actions. The character of the community and socio-political factors present in the area of operation largely define the extent to which the police acts - to arrest, search, apprehend, seize, or to deploy unconventional strategies.